THE RESTORATION OF THE SELFOBJECT. Issue 3 (3rd July 2018) - Magid, Barry; SHANE, ESTELLE
Abstract : Heinz Kohut insisted that, strictly speaking, the selfobject was an experience provided by the analyst's function, not a person. However, in light of an increasing body of mother-infant research into the bidirectionality of experience at all levels of development, and the consistent with the relational turn in self psychology, which emphasizes the roles of rhythmicity, mutuality and impact in the creation of attachment and a feeling of being understood, we maintain that it is time to restore the selfobject to personhood. Case material illustrates the role of the analyst's subjectivity in the creation of the selfobject experience, which is now conceptualized as part of a two-person psychology and relational interaction.